Bird richness at Sítio do Sol in Cabreúva, State of São Paulo, Brazil - Silva, Gabriel de Paula da; Lima, Lucas Renan Martins de; Capelli, João Gabriel Cerrati; Souza, Natália Lavínia Andrello; Aranha, Valéria Leite (Acta Scientiarum. Biological Sciences, 2024)
The Atlantic Forest biome has suffered great devastation but still possesses a vast biological and endemic richness, making its preservation essential. The Atlantic Forest fragments located in the interior of the state of São Paulo have not been studied as much as other areas, mainly in the municipality of Cabreúva. Therefore, this study aimed to characterize the bird richness of the Sítio do Sol property, in Cabreúva, São Paulo. The study was carried out from August 2021 to September 2022, covering seasonality. The findings revealed that 193 species were registered, distributed among 52 families, and 23 orders, with a predominance of the Passeriformes order and the Tyrannidae family. The most observed trophic guild among species was insectivorous, accounting for 78 (41%) species, followed by omnivorous with 59 (31%) species, carnivorous 18 (9%), frugivorous 16 (8%), granivorous 12 (6%), nectarivorous 8 (4%), and detritivorous species 2 (1%), with lower richness. This study is one of the few bird surveys carried out in the municipality of Cabreúva and indicates that even in small forest fragments, there is a considerable species richness. Developing more fauna surveys and management plans for the species present in the area is important to preserve these birds.